PELAS LENTES ELIASIANAS: A DINÂMICA CONSTITUTIVA DE SER PROFESSORA DE EDUCAÇÃO ESPECIAL NA ÁREA DA DEFICIÊNCIA VISUAL - Kautsky, Giselle Lemos Schmidel (2021)
In this study, we aim to systematize analyzes and notes on the constitutive dynamics of the work of Special Education teachers with visually impaired students enrolled in public schools of common education. For that, we gathered data on both personal and professional formation of the Special Education teacher and we made understandings about the working conditions in/of the schools where she performed her pedagogical function. We used the observation in context to develop a qualitative research, designed as a case study, based on the work of the Special Education teacher in the daily lives of three schools. We used contextual observation to follow the work of a Special Education teacher in the daily life of three schools. In this dynamic, we assume the theoreticalmethodological strategy of Eliasian process research. The production/collection of data was made through field diary records, questionnaires, interviews and searches for information in national and local documents that deal with Special Education, having the Brazilian Federal Constitution of 1988 as a time frame. We made the study in the presuppositions of the theory elaborated by Norbert Elias (1994, 1988, 2002, 2006, 2008), mainly in the conception of knowledge and individualization. Throughout the investigation process we assume the involvement-distancing (ELIAS, 1988, 2001) as a theoretical-methodological foundation and we also experience the peculiar way of Eliasian micro-macro analysis (SCHEFF, 2001; LOYAL; QUILLEY, 2004). We began our research with the knowledge that the initial formation and continued, together with other aspects of everyday work in schools, delineate significant elements in the constitutive dynamics of a teacher of special education in the visual deficiency. Aiming to expand this knowledge, in the course of the investigation, we asked about how (under what conditions) and from what (physical space, material, relationships inside and outside the school) the work of the Special Education teacher in the area of visual impairment was developed. In this way, we systematized, analyzed and gathered notes that support our thesis that the overlapping of political, historical and social dimensions, specific to our recent societies, has implications for the behavior and emotionalities of/in the realization of being a teacher. In this direction, the study results indicate that in order of being a Special Education teacher in the visual impairment area is marked by experiences prior to professional life, by complex formative learning, by the constitution of sui generis practices with visual impairment students and by inter -relationships with professionals in the educational space, as well. Yet, the existence of a Special Education teacher in the area of visual impairment does not escape the dependent and interdependent movements that underlie the dynamic of their work at school: educational project of the teaching system and the physical, material and pedagogical conditions for performing the professional work – a condition that makes it possible to underscore the meaning of the actions and purposes of the Special Education teacher's work in the area of visual impairment in regular schools.